A conquista da amamentação : o olhar da mulher - Machado, Márcia Maria Tavares (1999)
This work discusses the perceptions and experiences of the women who breastfed exclusively for a period of at least six months. In an attempt to find some responses, particularly with regard to the experiences of those mothers, we seek to portray their attitudes and the meaning that breastfeeding has for his mother, seeking to clarify what originated in the Group a predisposition to breastfeed exclusively. The study was conducted on the basis of the qualitative methodology, having been interviewed 13 mothers, whose speeches pointed important elements responsible for the successful breastfeeding. We have seen the complexity of the Act of breastfeeding, considered by many to be simple and can be experienced by all women and noted that the success of breastfeeding originated mainly, the meaning constructed by the same throughout your everyday life, absorbing and reinterpreting conceptions and experiences present before and during your experience in nursing. In addition, the motivation and perception of nursing process It is evidenced by experiences in the family, for building self-confidence and, primarily, strong determination to breastfeed, surpassing in this way, the different obstacles that present themselves to the conquest of breastfeeding.